Adjunctive Probiotics as Host Modulation Agent in Advanced Periodontitis: A Systematic Review of Randomized Controlled Trials - Cherry Erlin Lindo; Boy Muchlis Bachtiar; Claudia Isabella; Karina Natalie Natalie; Karina Putri Juwita (Scientific Dental Journal, 2024)
Periodontitis, a complex oral inflammation, poses health risks, especially in advanced stages. Traditional treatments like nonsurgical periodontal therapy (NSPT) have limitations, prompting exploration of adjunctive approaches like probiotics. This systematic review focuses on randomized controlled trials (RCTs) assessing probiotics' impact when used alongside NSPT for advanced periodontitis. Periodontitis, a chronic oral condition, requires effective interventions, especially in advanced stages marked by severe tissue damage. Probiotics, particularly Lactobacillus and Bifidobacterium, have gained attention for their potential in supporting oral health. This review aims to analyse RCTs exploring probiotics as adjuncts to NSPT in advanced periodontitis. From 59 identified studies, 5 met inclusion criteria, published between 2019 and 2021. These studies examined probiotics' effects on probing pocket depth (PPD) and clinical attachment level (CAL) in stage III/IV Grade C periodontitis. Variations in probiotic strains, formulations, and therapy durations were observed. Risk of bias assessment indicated generally low risks across selected studies. Findings on PPD reduction were inconclusive, with two studies favouring probiotics, while others showed minimal differences. CAL gain was observed in all three studies assessing it, but no significant differences between probiotics and control groups were found. The benefits of adjunctive probiotics in advanced periodontitis remain unclear, contributing to the lack of firm conclusions. While probiotics show promise in influencing periodontal parameters, the current evidence does not firmly establish their efficacy as adjuncts to NSPT in advanced periodontitis. Homogeneous RCTs with standardized protocols are crucial for a more comprehensive evaluation of probiotics' potential benefits in this context